2022
DOI: 10.3390/biology11060862
|View full text |Cite
|
Sign up to set email alerts
|

Gene Editing-Based Technologies for Beta-hemoglobinopathies Treatment

Abstract: Beta (β)-thalassemia is a group of human inherited abnormalities caused by various molecular defects, which involves a decrease or cessation in the balanced synthesis of the β-globin chains in hemoglobin structure. Traditional treatment for β-thalassemia major is allogeneic bone marrow transplantation (BMT) from a completely matched donor. The limited number of human leukocyte antigen (HLA)-matched donors, long-term use of immunosuppressive regimen and higher risk of immunological complications have limited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Genome editing (GE) can be considered among the most promising strategies to correct hereditary alterations in a variety of monogenic diseases, including hematopoietic pathologies [ 34 , 35 ]. Figure 2 depicts how CRISPR-Cas9 gene editing can be applied to β-thalassemia [ 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. CRISPR-Cas9 gene editing can be proposed for efficient correction of the NM_000518.5:c.118C>T thalassemia variant (HGVS nomenclature, β 0 39C>T traditional nomenclature) [ 45 ].…”
Section: The Impact Of Changes In the Expression Of Alpha-globin Gene...mentioning
confidence: 99%
“…Genome editing (GE) can be considered among the most promising strategies to correct hereditary alterations in a variety of monogenic diseases, including hematopoietic pathologies [ 34 , 35 ]. Figure 2 depicts how CRISPR-Cas9 gene editing can be applied to β-thalassemia [ 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. CRISPR-Cas9 gene editing can be proposed for efficient correction of the NM_000518.5:c.118C>T thalassemia variant (HGVS nomenclature, β 0 39C>T traditional nomenclature) [ 45 ].…”
Section: The Impact Of Changes In the Expression Of Alpha-globin Gene...mentioning
confidence: 99%
“…Single-mutation diseases such as SCD, represent ideal targets for gene editing. Moreover, the ability of gene editing to introduce targeted mutations that may cause a disease-modulatory effect made it possible to use a universal approach to target, in addition to SCD, the many different thalassemia mutations through the reactivation of the endogenous γ-globin gene [25][26][27][28][29][30][31][32]. Gene editing utilizes for the targeted introduction of point mutations or small deletions and insertions of the cells' endogenous DNA damage response mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, recent research found that disrupting the GATAA motif in the BCL11A erythroid enhancer resulted in a significant increase in HbF expression 9 . Fortunately, recent studies revealed that the disruption of the GATAA motif in BCL11A erythroid enhancer led to a substantial increase in HbF expression 10 .…”
Section: Introductionmentioning
confidence: 99%